THE DEVELOPMENT OF NATURAL SCIENCE LEARNING MODULES ORIENTED STRENGTHENING CHARACTER EDUCATION ON THE MATERIAL OF LIGHT AND ITS NATURE - Siti Murnah; Ahmad Syachruroji; Nana Hendracipta (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2022)
The development of this science learning module discussed about natural science lessons in elementary schools and includes strengthening student character education, because the reality in the field of natural science lessons is very boring. Through the development of natural science learning modules oriented towards strengthening character education, in this case they show many advantages in making the learning process become systematic and can be done independently anywhere and anytime, so that it can rehearsed students' character in the surrounding environment. The purpose of this study was to know the students responses and the feasibility study of developing natural science learning modules oriented towards strengthening character education on the material of light and its nature which developed according to the reviews of experts in product trials. Research and development is a method used to collect data, collect information from informants either in writing or orally, researchers collect data by conducting observation, in-depth interviews and documentation. Data analysis conducted in the field and after the data was collected. The results of this study suggest that the development of natural science learning modules is oriented towards strengthening character education on the material of lights and its nature is that there are assessments of student responses of 89,28%, material experts 95,22%, media experts 93.33%, and linguists 72,5%, from the results of the assessment that the natural science module oriented towards strengthening character education is appropriate for elementary school students to use independently or with a companion.The development of this science learning module discussed about natural science lessons in elementary schools and includes strengthening student character education, because the reality in the field of natural science lessons is very boring. Through the development of natural science learning modules oriented towards strengthening character education, in this case they show many advantages in making the learning process become systematic and can be done independently anywhere and anytime, so that it can rehearsed students' character in the surrounding environment. The purpose of this study was to know the students responses and the feasibility study of developing natural science learning modules oriented towards strengthening character education on the material of light and its nature which developed according to the reviews of experts in product trials. Research and development is a method used to collect data, collect information from informants either in writing or orally, researchers collect data by conducting observation, in-depth interviews and documentation. Data analysis conducted in the field and after the data was collected. The results of this study suggest that the development of natural science learning modules is oriented towards strengthening character education on the material of lights and its nature is that there are assessments of student responses of 89,28%, material experts 95,22%, media experts 93.33%, and linguists 72,5%, from the results of the assessment that the natural science module oriented towards strengthening character education is appropriate for elementary school students to use independently or with a companion.